OPTIMASI KOMBINASI SETIL ALKOHOL DAN LANOLIN PADA FORMULA BALSAM STIK DENGAN METODE SIMPLEX LATTICE DESIGN - Ratih Dyah Pertiwi; Fayza Maghfira Solachudin; Hermanus Ehe Hurit (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
A Balsam stick is a stick-shaped balsam that is made easier to use. Stiffening agents and emollients are needed to maintain the consistency of the balsam stick. This study aims to determine the optimum formula for balsam sticks with a combination of cetyl alcohol and lanolin. Using the Simplex Lattice Design method, the optimum formula for balsam sticks is obtained through the Design Expert version 13. The analysis results of spreadability, adhesion, and hardness were obtained using the ANOVA test. The optimum formula was obtained with a combination of cetyl alcohol concentration of 40.5% and lanolin 59.5% with a desirability value of 1.000 and the predicted results of spreadability of 3.506 cm, adhesion of 11.597 seconds, and hardness of 9.259 mm. In the evaluation results carried out in the laboratory, the value of the spreadability test was 3.62 ± 0.08 cm, the adhesion test was 10.92 ± 0.44 seconds, and the hardness test was 9.029 ± 0.31 mm. The verification results of the optimum formula were a sig 2-tailed value on spreadability of 0.139, adhesion of 0.120, and hardness of 0.328 where sig 2-tailed >0,05, indicating no significant difference. This suggests that the optimum formula of balsam sticks gives good results and meets the requirements.